PENYULUHAN HUKUM TENTANG BANTUAN HUKUM BAGI PEGAWAI NEGERI PADA POLRI - Rahman Amin; Alfin Pratama; Muhammad Fikri Al Aziz (Abdi Bhara, 2022)
Every Indonesian citizen has human rights that areguaranteed constitutionally in the 1945 Constitution, one ofwhich is the guarantee of protection and legal equality withoutany differences based on the principle of equality before thelaw, including the right to obtain legal assistance in facing thejudicial process.Especially within the Indonesia NationalPolice, legal assistance is the right of every civil servant in theNational Police who is facing legal problems in order to helpresolve these legal problems, both through the judiciary andoutside the judiciary. However, in reality, the right to obtainlegal assistance is still not well known and understood by civilservants at the National Police so that it is important to carryout community service activities in the form of legal counselingon legal assistance for civil servants at the National Police. Thetarget of this activity is civil servants at the National Police whoserve in the Cangkuang Police Station, Bandung Police, whichis located at Nagrak street, Number 58, Ciluncat, CangkuangDistrict, Bandung Regency, West Java Province. Theimplementation of this activity includes the stages ofpreparation, implementation and evaluation. The target to beachieved in this activity is the implementation of counselingactivities so that they can provide knowledge and understandingabout the right to obtain legal assistance, as well as produceoutputs in the form of reports on the results of activitiespublished in national journals with ISSN, and can be used asmaterial for enrichment of lecture material for students.